HARDINESS RELATIONSHIP BETWEEN STRESS WITH SORT OF STUDENTS IN THESIS - Awida Tri Sekariansah; Hastaning Sakti (Jurnal EMPATI, 2013)
Thesis is defined as a scientific essay that must be written by students as part of the final terms of academic education (in KBBI, 2011, h.1325). Based on the observations made by Gunawati, et. all (2006) found that the daily behavior of students who are preparing theses indicate the presence of symptoms of stress. Stress is a condition of the physical and psychological stress due to the demands of the self and the environment. This study aimed to test empirically the relationship between Stress Hardiness In Preparing Students in the Faculty of Engineering Thesis Department of Mechanical Engineering, University of Diponegoro in Semarang.Total population in the study of 60 people, due to the limited number of population, the study will use the study population. The sampling technique used accidental sampling. Retrieval of data using the Student Stress Scale with 24 items Thesis Preparation (α = 0.867), and the Hardiness Scale with 24 items (α = 0.837). Data analysis using simple regression analysis.The results showed a correlation coefficient rxy = - 0.553 with p = 0.000 (p <0.01), which means showed no significant negative relationship between hardiness to stress on students in the thesis. That is, the higher the lower the stress Hardiness students in the thesis, and vice versa. The hardiness contribute to stress by 30.6% of students in the thesis, and the remaining 69.4% are other factors suspected to influence the stress mahasciswa thesis.